A Study of Generative Partnership. Issue 1 (8th April 2020) - Zinck, Kirk; Neel, Joanna
Abstract : This phenomenological study suggests that generativity, long conceptualized as a stage of individual psychosocial development, is a collaborative experience in the developmental trajectory of some marriages and long‐term partnerships. This new knowledge was developed through exploring the lived experience of 10 middle‐aged and older couples who participated in this research. Termed "generative partnership, " this collaborative experience includes 3 facets: embracing generative identity, contributing talents and resources, and passing it on. Findings suggest that generative partnerships enhance satisfaction and vitality in relationships at midlife and beyond as couples encounter the opportunities and challenges of growing old together.